Optimalisasi Penentuan Posisi Access Point Pada Ruang Tertutup Menggunakan Algoritma Genetika - Misbahuddin; Djul Fikry (DIELEKTRIKA, 2023)
WiFi is a term used for wireless network devices (WLAN) based on IEEE 802.11 standard. Access Point is a WLAN device that is used as a transmitter or receiver. One of the parameters that can determine the performance of a WiFi is the coverage area of an access point. Placement it is not appropriate with environmental conditions will cause some of an area that is not covered or a blankspot area. In this research, the position of the access point was optimized using a genetic algorithm based on position and coverage area. Total coverage area is obtained by determining the union coverage area of all access points which appropriate with the range that is determined using indoor propagation model. From the research results, the most optimal number of access points is 5 access points. The existing condition with 5 access points has a coverage area of 75.27%, while optimization using 5 access points has a coverage area of 96.64%. The optimization can increase the coverage area by 21.38% and reduce the blank spot area to 3.36%.